(untitled) (JURNAL IBU DAN ANAK, 2020)
Abstract Fisiology anatomy change in the pregnant women make a complaints that often appear one which is sleep disorder. 50% of third trimester pregnant womens in Payung Sekaki Health Community Center experience sleep disorder. One way to overcome is with pregnancy exercise. The research aim is for knowing the effect of pregnancy exercise on sleep quality in third trimester pregnant women in Health Community Center Payung Sekaki Pekanbaru on March until June 2019. The research used pre experiment with one group pretest and post test design. Populations this research is all pregnant women in the third trimester at Payung SekakiPekanbaru Health Community Center and samples this research was 29 people taken by purposive sampling technique. Data the sleep quality in research use Pittsburgh Sleep Quality Index (PSQI) questionnaire. Univariate and bivariate data analysis using the Wilcoxon test. Result the research show there is increase sleep quality in third trimester pregnant women with p value 0,000 (p<0,005) that means there is significant effect ofsleep quality in third trimester pregnant women before and after pregnancy exercise.Suggestions in this study are that the research site conducts a pregnancy exercise program an invites pregnant women to take part in pregnancy exercises regularly.